Performance Analysis in Game Sports : Concepts and Methods - Lames, Martin (Springer International Publishing, 2023)
This book offers a comprehensive overview on the methods and concepts of theoretical and practical performance analysis. Observational systems for action detection and tracking systems for position detection are introduced, starting from basic methodological principles. The issue of reliability testing is addressed for both methods, and examples of successful applications are provided. The distinction between theoretical and practical performance as essential conceptual achievement is explained in two separate chapters. Most recent theoretical models of game sports are presented, including the dynamical systems perspective, stochastic modelling, and contingency or chance as part of the game. The practical chapter introduces the concept of comprehensive performance analysis as appropriate background. It deals with qualitative methods used for assessing player and team performances, strategy development, and methods and principles of video tactic training for successful transfer of the results of analyses. The book will be of value to all with an interest in the dramatically increasing impact of performance analysis in game sports